Faktor-Faktor Yang Mempengaruhi Intensi Berwirausahaan Pada Kalangan Mahasiswa (Studi Kasus Mahasiswa Feb Ums ) - Ariyani, Lilis, Jati Waksito. S.E., M.Si (2016)
This study aimed to examine the effect of self-efficacy requirements, subjective norms, and pedidikan to the intention entrepreneurship among students at the FEB students study at UMS. sample of 91 respondents drawn from each progdi in Surakarta Muhammadiyah University economics faculty. The sampling technique in this research is using purposive random sampling technique. Methods of data analysis used to test the validity, reliability test, normality test, mltikolinearitas, multiple linear regression tests, hipotesisuji t, F test, and R². The results showed that self-efficacy variable, subjective norm, and education significantly influence entrepreneurial intense. While the test results F analysis shows that self- efficacy variable, subjective norm and education jointly significant effect on entrepreneurship intense. So that the model used is fit. The results of test analysis coefficient of determination (R2) obtained by the coefficient of determination (R2) of 0.364